Epidemiology, Ecology and Prevention of Plague in the West Nile Region of Uganda: The Value of Long-Term Field Studies - Eisen, Rebecca J.; Atiku, Linda A.; Enscore, Russell E.; Mpanga, Joseph T.; Acayo, Sarah; Mead, Paul S.; Apangu, Titus; Yockey, Brook M.; Borchert, Jeff N.; Beard, Charles B.; Gage, Kenneth L. (The American Journal of Tropical Medicine and Hygiene., 2021)
Plague, a fleaborne rodent-associated zoonosis, is a neglected disease with most recent cases reported from east and central Africa and Madagascar. Because of its low incidence and sporadic occurrence, most of our knowledge of plague ecology, prevention, and control derives from investigations conducted in response to human cases. Long-term studies (which are uncommon) are required to generate data to support plague surveillance, prevention, and control recommendations. Here we describe a 15-year, multidisciplinary commitment to plague in the West Nile region of Uganda that led to significant advances in our understanding of where and when persons are at risk for plague infection and how to reduce morbidity and mortality. These findings provide data-driven support for several existing recommendations on plague surveillance and prevention and may be generalizable to other plague foci
Keywords: Epidemiology; Ecology; Plague; West Nile Region; Uganda